PERBANDINGAN EFEKTIVITAS MEDIA POP-UP BOOK & VIDEO ANIMASI KARTUN TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA ANAK SD (Tinjauan Siswa SDN Kuripan 2 Banjarmasin) - Stevani Stevani; Raden Harry Dharmawan Setyawardhana; Beta Widya Oktiani; I Wayan Arya Krishnawan Firdaus (Dentin, 2024)
Background: Dental and oral health is part of overall body health. In Indonesia, dental and oral health problems are still relatively high and the proportion of correct dental and oral health knowledge among elementary school children is still low. Providing health education through pop up books and animated cartoon videos can be used as information media to increase knowledge of dental and oral health in elementary school children. Objective: This study aims to analyze dental and oral health knowledge in elementary school children through pop up book media and animated cartoon videos on dental and oral health knowledge in elementary school children at SDN-SN Kuripan 2 Banjarmasin, Banjar Regency. Methods: Using a true experimental design with a pretest-posttest with control design with a simple random sampling technique. The research was carried out at SDN-SN Kuripan 2 Banjarmasin, Banjar Regency with a sample of 76 respondents. Results: The results of the T-Test Normality test data analysis showed that there was no difference in dental and oral health knowledge among elementary school children and before and after counseling (pop up book: p=13.16; animated cartoon video: p=13.63), There was no difference in dental and oral health knowledge in elementary school children between pretest and posttest (pop up book: p= 13.16; animated cartoon video: p=13.63). The results of the Mann Whitney test data analysis were p=0.097, which means oh, it is accepted, indicating there is no difference in knowledge of dental and oral health among elementary school children. Conclusion:. The conclusion of this research is that health knowledge education through pop up books and animated cartoon videos is equally effective for dental and oral health knowledge in elementary school children.Keywords: Counseling, dental and oral health, Pop Up Book, animated cartoon video ABSTRAKLatar belakang: Kesehatan gigi dan mulut merupakan bagian dari kesehatan tubuh secara keseluruhan. Di Indonesia masalah kesehatan gigi dan mulut masih tergolong tinggi dan proporsi pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar yang benar masih rendah. Pemberian penyuluhan kesehatan melalui pop up book dan video animasi kartun dapat dijadikan sebagai media informasi untuk meningkatkan pengetahuan Kesehatan gigi dan mulut pada anak sekolah dasar. Tujuan: Penelitian ini bertujuan untuk menganalisis pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar melalui media pop up book dan video animasi kartun terhadap pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar pada siswa SDN-SN Kuripan 2 Banjarmasin, Kabupaten Banjar. Metode: Menggunakan true eksperimental design dengan rancangan pretest-postest with control design dengan teknik pengambilan sampel simple random sampling. Penelitian dilaksanakan di SDN-SN Kuripan 2 Banjarmasin, Kabupaten Banjar dengan sampel berjumlah 76 responden. Hasil: Hasil analisis data uji Normalitas T-Test menunjukkan tidak ada perbedaan pengetahuan Kesehatan gigi dan mulut pada anak sekolah dasar dan sebelum dan setelah penyuluhan (pop up book: p=13,16; video animasi kartun: p=13,63), tidak ada perbedaan pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar antara pretest dan posttest (pop up book: p= 13,16; video animasi kartun: p=13,63). Hasil analisis data uji Mann Whitney p=0,097 yang berarti oh diterima menunjukkan tidak ada perbedaan pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar Kesimpulan:. Kesimpulan penelitian ini adalah penyuluhan pengetahuan kesehatan melalui pop up book dan video animasi kartun sama efektif untuk pengetahuan kesehatan gigi dan mulut pada anak sekolah dasar.